Stability formulations and design of buckling-restrained braces considering stiffness degradation. (March 2022) - Yue, Yanchao; Jia, Kai; Chen, Tangbing; Li, Changxin; Bai, Yongtao
Abstract: The existing stability design methods of buckling restrained braces (BRBs) ignore the stiffness contribution of the filled concrete and core plate, which leads to some error in the calculation of the overall stability of a BRB and cannot accurately describe its buckling mechanism. In this study, theoretical analysis was carried out considering the partial stiffness of the filled concrete and the core plate to investigate the calculation formula of the overall stability of BRBs, and numerical analysis was carried out using different compound sections of core plates to obtain the stiffness reduction factor of filled concrete and the core plate. The results of the analysis showed that the stability calculation formula in this study could predict the buckling behavior of a BRB accurately and was applicable to BRBs with different compound sections. In addition, through the analysis of the working performance of BRBs under different clearance-to-thickness ratios and frictions, the influence of varying clearance and friction on the performance indexes of braces are obtained and some suggestions are put forward for the reasonable values of clearance and friction.